PENGARUH EXPERIENTIAL MARKETING DAN SERVICESCAPE TERHADAP REPURCHASE INTENTION MELALUI KEPUASAN KONSUMEN PADA CAFÉ ONE REFINERY DI KOTA PEKANBARU - Pangestu Bagus Febrian; Jushermi Jushermi; Nursanti Aida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
At this time, the development of the food and beverage industry business sector in Indonesia is growing rapidly. This increasingly fierce and increasing business competition requires business people to maximize their business performance in order to compete globally, as well as maintain their business. One of the important strategies that need to be considered by business people is Experiential Marketing. One of the cafes that implements Experiential Marketing is One Refinery Pekanbaru. This study aims to examine the effect of Experiential Marketing and Servicescape on Repurchase Intention through consumer satisfaction at One Refinery Pekanbaru café. The analysis technique used is path analysis. The number of samples taken as many as 105 respondents by accidental sampling method. Data was collected by distributing questionnaires. Based on the results of the study, it was found that the Experiential Marketing and Servicescape variables had a significant effect on consumer satisfaction, the consumer satisfaction variable had a significant effect on Repurchase Intention, and the Experiential Marketing and Servicescape variables had a significant effect on Repurchase Intention through consumer satisfaction.Keywords : Experiential Marketing, Servicescape, Consumer Satisfaction, Repurchase Intention